Challenges Over Two Semantic Repositories - OWLIM and AllegroGraph - Paria Tajabor; Tara Raafat (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The purpose of this research study is exploring two kind of semantic repositories with regards to various factors to find the best approaches that an artificial manager can use to produce ontology in a system based on their interaction, association and research. To this end, as the best way to evaluate each system and comparing with others is analysis, several benchmarking over these two repositories were examined. These two semantic repositories: OWLIM and AllegroGraph will be the main core of this study.  The general objective of this study is to be able to create an efficient and cost-effective manner reports which is required to support decision making in any large enterprise.